KERAGAMAN POLA MEMBANGUN KAPABILITAS INOVASI ORGANISASIONAL PADA INDUSTRI SKALA KECIL MENENGAH - Siyamtinah Siyamtinah (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2010)
The aims of this study were to analyze for the pattern diversity of organizational innovationcapability building and what factor caused it among Small and Medium Business (SMB) inSemarang.The study used seven factors of determinant of innovation capability. The factorwere human resource capability, technology usage, external interactions, marketing capability,production/operation capability, new product development, and research and development.The study also propose 2 (two) factors that were used to test what factors causes the patterndiversity of innovation capability building. The factors are business size and business age.Based on literatures reviews and questionnaire result, for 101 managers of SMB and t-tetsanalize, succeed that business size caused pattern diversity of organizational innovationcapability building among SMB for four factors.The factors were human resource capability,technologi usage, marketing capability and research and development. The followed analysis,business age caused pattern diversity of organizational innovation capability building amongSMB for four factors. The factors were external interaction, marketing capability, technologiusage and research and development.Keywords : Innovation Capability, Pattern Diversity,SMB